2016
DOI: 10.1080/01635581.2016.1145244
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Potentiates Growth Inhibitory Effects of Rapamycin inPTEN-deficient Lipoma Cells by Suppressing p70S6 Kinase Activity

Abstract: Patients with phosphatase and tensin homolog (PTEN) hamartoma tumor syndrome and germline mutations in PTEN frequently develop lipomatosis, for which there is no standard treatment. Rapamycin was shown to reduce the growth of lipoma cells with heterozygous PTEN deficiency in vitro, but concomitantly induced an upregulation of AKT phosphorylation. Since it was shown that resveratrol stabilizes PTEN, we asked whether co-incubation with resveratrol could suppress the rapamycin-induced AKT phosphorylation in PTEN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Our results indicate that Res shows no substantial effect on the mRNA level of PTEN in HCT116 cells, or the total protein level of PTEN. However, Res can apparently decrease the phosphorylation of PTEN, which is consistent with the previous studies that PTEN is involved in the anticancer effect of Res in cancer cells (45)(46)(47). To further unveil the relationship between BMP7 and PTEN, we introduced the BMP7 recombinant adenovirus and a specific antibody.…”
Section: Discussionsupporting
confidence: 62%
“…Our results indicate that Res shows no substantial effect on the mRNA level of PTEN in HCT116 cells, or the total protein level of PTEN. However, Res can apparently decrease the phosphorylation of PTEN, which is consistent with the previous studies that PTEN is involved in the anticancer effect of Res in cancer cells (45)(46)(47). To further unveil the relationship between BMP7 and PTEN, we introduced the BMP7 recombinant adenovirus and a specific antibody.…”
Section: Discussionsupporting
confidence: 62%
“…It was previously shown that rapamycin upregulates Akt phosphorylation ( Leipert et al, 2016 ; O'Reilly et al, 2006 ; Schmid et al, 2014 ), which is already elevated in Pten cKO retinas ( Cantrup et al, 2012 ; Tachibana et al, 2016 ). We thus asked whether pAkt levels were further increased in animals treated with rapamycin.…”
Section: Resultsmentioning
confidence: 96%
“…Pten is a negative regulator of PI3K, and mTOR signalling is activated downstream of PI3K so, in the absence of PTEN, mTOR signalling is elevated ( O'Reilly et al, 2006 ). An open-label drug trial has been started with the mTOR inhibitor sirolimus (alternative name for rapamycin) to treat PHTS patients, and this drug has shown some efficacy in inhibiting the growth of lipomas, which are a type of hamartoma ( Leipert et al, 2016 ; Schmid et al, 2014 ; Wang et al, 2007 ). We previously reported that mTOR signalling is upregulated in Pten cKO retinas ( Cantrup et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, published studies on the role of mTOR in adipose tissue browning have been paradoxical. It is reported that Res influences mTOR complex 1 (mTORC1) or its downstream site P70S6 (16). In this study, we aimed to elucidate the role of Res in the formation of brown-like adipocytes in 3T3-L1 and explore mechanisms related to mTORC1 underlying this process.…”
mentioning
confidence: 99%